How organizational learning affects innovation in SMEs: the case of information and communication technologies in Malaysia - Zandi Pour Joopari, GholamReza; Sulaiman, Mohamed; Naysary, Babak; Mohamed Salim, Islam (2013)
This research is an attempt at empirically testing the link between organizational learning and innovation in SMEs in Malaysia. According to the literature, organizational learning and innovation are crucial factors in firms’ performance but the focus of present study is to determine whether organizational learning lead to innovation. This study was conducted in a sample of 278 SMEs in Malaysia. The hypotheses in this study were developed to examine the relationship between organizational learning (OL) and innovation (I). To conduct the analysis we made use of Analysis of Moment Structure (AMOS 18.0) and SPSS 17.0. The findings approve the hypotheses implying a significant positive relationship between OL and I. Several implications for management and policy are also discussed in light of the findings of this study.